DIFFERENCES IN COMMUNICATING TRUST TO STAKEHOLDERS BY CHINESE AND US TECHNOLOGY LEADERS - CHMIELEWSKA-MUCIEK, DOROTA; Jakubczak, Jacek; Marzec-Braun, Patrycja (Organizacja i Kierowanie, 2023)
The ability of technology leaders to build trust is one of the most important challenges today. The key to building trust is clear and consistent communication to retain existing stakeholders and encourage collaboration. Communicating trust in the case of Chinese and U. S. technology leaders influences their success but differs in the volume of communication and the number, richness and density of trust-related phrases used. The purpose of this article was to identify differences in the communication of trust by Chinese and U. S. tech leader companies. For this purpose, a conceptual content analysis of 80 annual reports from years 2015–2022 of 5 USA and 5 Chinese tech leaders was used. As the content analysis showed, Chinese companies’ communication with stakeholders is clearly more elaborate, using a greater overall number of trust phrases and displaying greater linguistic richness in the phrases used compared to those of U. S. companies. On the other hand, US companies’ communication with stakeholders is more saturated than that of Chinese companies.